Numerical Investigation of the Production Behavior of Methane Hydrates under Depressurization Conditions Combined with Well-Wall Heating - Ruan, Xuke; Li, Xiao-Sen; Xu, Chun-Gang (Energies, 2017)
In this study, a 2D hydrate dissociation simulator has been improved and verified to be valid in numerical simulations of the gas production behavior using depressurization combined with a well-wall heating method. A series of numerical simulations were performed and the results showed that well-wall heating had an influence enhancing the depressurization-induced gas production, but the influence was limited, and it was even gradually weakened with the increase of well-wall heating temperature. Meanwhile, the results of the sensitivity analysis demonstrated the gas production depended on the initial hydrate saturation, initial pressure and the thermal boundary conditions. The supply of heat for hydrate dissociation mainly originates from the thermal boundaries, which control the hydrate dissociation and gas production by depressurization combined with well-wall heating. However, the effect of initial temperature on the gas production could be nearly negligible under depressurization conditions combined with well-wall heating.